Pore Properties of the Lacustrine Shale in the Upper Part of the Sha-4 Member of the Paleogene Shahejie Formation in the Dongying Depression in East China - Ziyi Wang; Liuping Zhang; Yuan Gao; Wenxiu Yang; Yongshi Wang; Huimin Liu; Zhaoyang Li; Shanshan Zhou (Geofluids)
Lacustrine shales hold a huge potential oil resource in China. Pore properties (pore volume, diameter, specific surface area, and fractal dimensions) and their relationships with geological factors (mineralogy, insoluble organic carbon, burial depth, and vitrinite reflectance) are critical for evaluating shale oil resource. However, the factors controlling pores for lacustrine shale oil remain unclear, as the relationships between pore properties of Soxhlet-extracted samples and geological factors have not been studied using multivariate analytical methods. In this paper, the samples from the lacustrine shale in the upper part of the Sha-4 Member of the Paleogene Shahejie Formation in the Dongying Depression were tested with a set of experiments including Soxhlet (solvent) extraction, X-ray diffraction mineral analysis, insoluble organic carbon, vitrinite reflectance, and low-pressure CO2 and N2 adsorption experiments. The micromesopore volume varies from 0.003 cm3/g to 0.045 cm3/g. The relationships of pore properties with geological factors were studied with partial least square regression analysis (PLSR analysis, a powerful multivariate regression analysis). The results of the PLSR analyses indicate that clay minerals and carbonates are two key factors affecting the pore properties of the lacustrine shale. Compared with marine shales, more clay minerals in the lacustrine shale make them become more important for controlling pores than organic matter. The PLSR results also illustrate that the shale with higher pore volume contains more clay minerals and fewer carbonates and thus is unfavorable for hydraulic fracturing. Therefore, the shale with high micromesopore volume may be unfavorable for shale oil production. The shale with the modest micromesopore volume (~0.036 cm3/g), relatively high content of brittle minerals (~71 wt%), and low clay mineral content (~29 wt%) is conducive to both oil storage and hydraulic fracturing for the development of the Es4U shale oil in the Dongying Depression in East China.